2015
DOI: 10.1371/journal.pone.0116695
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Postural Control in Healthy Men at Moderate Altitude (1630 M and 2590 M): Data from a Randomized Trial

Abstract: ObjectivesIntact postural control is essential for safe performance of mountain sports, operation of machinery at altitude, and for piloting airplanes. We tested whether exposure to hypobaric hypoxia at moderate altitude impairs the static postural control of healthy subjects.MethodsIn 51 healthy men, median age 24 y (quartiles 20;28), static control was evaluated on a balance platform in Zurich, 490 m, and during a 4-day sojourn in Swiss mountain villages at 1630 m and 2590 m, 2 days each. The order of altitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 15 publications
8
28
1
Order By: Relevance
“…Because the CNS requires a supply of oxygen to function, it is reasonable to assume that central processing and integration of the sensory inputs necessary to maintain balance and postural stability and process auditory information would be impaired by hypoxia. Previous studies have cited evidence of hypoxia-induced postural sway [93,94] and hypoxia-reduced equilibrium, primarily as a result of impairments related to visual function [95], and are consistent with a previous study [96] documenting significantly increased anteroposterior sway in the absence of visual cues during both slow-and rapid-onset hypoxia. Furthermore, previous studies also have found hypoxia-related deficits in auditory sensitivity, steady-state responses of auditory-evoked potentials and central auditory processing [97][98][99], suggesting that, similar to mTBI, hypoxia-mediated deficits involve compromised auditory processing at the level of the brainstem and CNS.…”
Section: Feasibility Of Using Normobaric Hypoxic Stress In Mtbi Reseasupporting
confidence: 88%
“…Because the CNS requires a supply of oxygen to function, it is reasonable to assume that central processing and integration of the sensory inputs necessary to maintain balance and postural stability and process auditory information would be impaired by hypoxia. Previous studies have cited evidence of hypoxia-induced postural sway [93,94] and hypoxia-reduced equilibrium, primarily as a result of impairments related to visual function [95], and are consistent with a previous study [96] documenting significantly increased anteroposterior sway in the absence of visual cues during both slow-and rapid-onset hypoxia. Furthermore, previous studies also have found hypoxia-related deficits in auditory sensitivity, steady-state responses of auditory-evoked potentials and central auditory processing [97][98][99], suggesting that, similar to mTBI, hypoxia-mediated deficits involve compromised auditory processing at the level of the brainstem and CNS.…”
Section: Feasibility Of Using Normobaric Hypoxic Stress In Mtbi Reseasupporting
confidence: 88%
“…Several winter and summer mountain sports were investigated by researchers based worldwide [59][60][61], and their papers focus on a wide range of subjects, i.e., sport tourism events and their economic impact [62,63], climate change and winter sports [64,65] or health aspects of sports activities in mountain regions, such as high altitude illness [66][67][68][69][70][71], thrombosis and pulmonary embolism [72], hand injuries [73,74] or facial traumas [75,76]. Moreover, some studies list many sports activities that can be practiced in mountain areas in winter and summer, such as mountaineering, climbing, downhill skiing, alpine skiing, ski mountaineering, hiking, cross-country biking, mountain racing, paragliding, canyoning and snowboarding [75,[77][78][79][80][81][82][83][84][85].…”
Section: Mountain Tourism and Sportsmentioning
confidence: 99%
“…Besides, an acute exposure to both hypobaric hypoxia (HH) and normobaric hypoxia (NH) leads to significant alteration in PC 2,4,[19][20][21] . Recently, we suggested that PC was more altered in HH than in NH 4 at rest.…”
mentioning
confidence: 99%